The 1st International Electronic Conference on Catalysis Sciences 2020
DOI: 10.3390/eccs2020-07552
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Behavior of Organodiselenides: Pro-Oxidant to Antioxidant

Abstract: Over the years, organodiselenides have emerged as the biologically relevant class of molecules. On one hand, such compounds are known for pro-oxidant effects leading to toxicity in biological systems. On the other hand, there are growing evidences about their bio-mimetic activities as catalysts such as glutathione peroxidase (GPx)-like activity. Our recent work has explored this paradoxical behavior of diselenides in developing antioxidants and/or anticancer agents. For this, a number of alkyl and aryldiseleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…315 The -SeH group attached to a pyridine ring undergoes tautomerization to form a selone, i.e., the R-CQSe has greater chemical stability than that of R-SeH, which is responsible for the reactive oxygen species (ROS) scavenging process and participates in the GPX-like cycle of some OSeCs. 25,316 As commented above, in mice, diphenyl diselenide is metabolized, and there was a clear rupture of the Se-C bond 122 and the release of Se to the inorganic Se pool that can feed the synthesis of selenoproteins. Although HSe À derived from the metabolism of diphenyl diselenide can also react with electrophilic forms of Hg, the increase in the excretion of Hg from the body of methylmercury-treated mice cannot be explained by the formation of HgSe salts.…”
Section: Potential Molecular Mechanisms Involved In the Pharmacologic...mentioning
confidence: 92%
See 1 more Smart Citation
“…315 The -SeH group attached to a pyridine ring undergoes tautomerization to form a selone, i.e., the R-CQSe has greater chemical stability than that of R-SeH, which is responsible for the reactive oxygen species (ROS) scavenging process and participates in the GPX-like cycle of some OSeCs. 25,316 As commented above, in mice, diphenyl diselenide is metabolized, and there was a clear rupture of the Se-C bond 122 and the release of Se to the inorganic Se pool that can feed the synthesis of selenoproteins. Although HSe À derived from the metabolism of diphenyl diselenide can also react with electrophilic forms of Hg, the increase in the excretion of Hg from the body of methylmercury-treated mice cannot be explained by the formation of HgSe salts.…”
Section: Potential Molecular Mechanisms Involved In the Pharmacologic...mentioning
confidence: 92%
“…, the R–CSe has greater chemical stability than that of R-SeH, which is responsible for the reactive oxygen species (ROS) scavenging process and participates in the GPX-like cycle of some OSeCs. 25,316…”
Section: Potential Molecular Mechanisms Involved In the Pharmacologic...mentioning
confidence: 99%
“…Organoselenium compounds have nowadays received a great attention as potential medicinal agents, crucial applications in synthetic organic chemicals, building block of complex molecules, and in material sciences . Additionally, it has been found that organoselenium compounds have dual characteristics, acting as an antioxidant for healthy cells and a pro-oxidant for cancer cells . Due to their utility in organic synthesis, many classes of organoselenium compounds have been studied to date. , …”
Section: Introductionmentioning
confidence: 99%